2011
DOI: 10.1590/s1981-77462011000200008
|View full text |Cite
|
Sign up to set email alerts
|

Violência no trabalho em saúde: análise em unidades básicas de saúde de Belo Horizonte, Minas Gerais

Abstract: O presente estudo buscou investigar e compreender a violência vivenciada em unidades básicas de saúde (UBSs) da perspectiva dos processos de trabalho em saúde. A caracterização da violência nesse contexto, ao identificar e compreender os elementos da produção desse fenômeno, contribui para o seu enfrentamento. De cunho descritivo-exploratório, para a coleta de dados a pesquisa utilizou grupos focais e entrevistas com usuários, trabalhadores e gestores do serviço de saúde. O estudo mostra as consequências e os … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
14

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 9 publications
1
33
0
14
Order By: Relevance
“…Other studies showed association to employee dissatisfaction (9)(10) , demotivation to work (10) , decreased professional commitment (5) , damage to teamwork, experiences working under pressure and physical overload (12) .…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Other studies showed association to employee dissatisfaction (9)(10) , demotivation to work (10) , decreased professional commitment (5) , damage to teamwork, experiences working under pressure and physical overload (12) .…”
Section: Discussionmentioning
confidence: 98%
“…Victims of workplace violence have been concerned about this issue (10,16) , which is linked to the discontent from their experiences and to consequences of worker safety. Victims of workplace violence have experienced feelings of fear and insecurity (10) , suggesting damage to workers' health.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations